Is our knowledge of voice and silence in organizations growing? Building bridges and (re)discovering opportunities - Knoll, M.; Wegge, J.; Unterrainer, C.; Silva, S.; Jonsson,T. (German Journal of Human Resource Management: Zeitschrift für Personalforschung, 2016)
This article has three objectives. Firstly, we seek to demonstrate the relevance of voice and silence – that is, whether employees contribute or withhold information, ideas, views and/or concerns at work – for the sustainable development of individuals, organizations and societies. Our second objective is to identify emerging (and enduring) issues – conceptual, theoretical and methodological – that have not yet been adequately addressed in voice and silence research. These issues include the relationship between voice and silence, how they may manifest in organizations, their manifold antecedents inside and beyond organizational boundaries, their potentially positive and negative effects for internal and external stakeholders, and methodological questions. The third objective is to propose opportunities for addressing these issues with the ultimate aim to build a broader and more integrative approach to the nature of silence and voice and their antecedents and consequences. These opportunities include a multi-level model specifying elements and processes leading to individual and collective voice and silence, approaches to voice and silence that have received little attention in organizational research so far, and methodological developments that might reveal new facets of voice and silence. Based on these elaborations, we derive avenues for practitioners who are concerned with promoting voice and preventing/overcoming silence in organizations.